Pola Pendidikan Islam Pada Periode Dinasti Umayyah - Rahimi Rahimi (Program Studi Pendidikan Sejarah Universitas Riau, 2021)
History of Islamic education is intrinsically very closely related to the history of Islam. Periodization of Islamic education is always in a period of Islamic history itself. Along with it, education in period of Dynasty Umayyah have had several institutions such as: Pole, Mosque and Literature Assembly. There are various and multilevel materials that is taught. And teaching method was not the same. In this paper, the Methods used by the author is Library Research and historical approaches by examining of a number of books, magazines, articles, and other references that are relevant to this paper by taking the essence, then author develop more. From this paper, the author concluded that the education pattern of the Dynasty Umayyah period continued education of the Khilafat ar Rasyiddin period, despite there was its own differences and developments.